Revitalizing the Muhammadiyah: Jamaah-Based Da’wah Movement Da'wah in the Digital Transformation Era - Rahmat Dipuro; Edy Purwanto; Saukani Nur Akbar; Heri Rifhan Halili (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
The Jamaah-Based Da’wah Movement (Gerakan Jamaah Dakwah Jamaah/GJDJ) represents one of Muhammadiyah’s strategic paradigms in developing a community-based da’wah system that emphasizes participatory, collective, and sustainable religious empowerment. This study was conducted in three Muhammadiyah branches and five sub-branches located in urban and semi-urban areas of South Sumatra Province that actively implement the GJDJ program. Within the dynamics of contemporary society, GJDJ faces serious challenges, including the weakening of social solidarity, the rise of urban individualism, digital transformation, and the shift of da’wah orientation toward institutional rather than communitarian approaches. This study aims to analyze the transformation of Muhammadiyah’s GJDJ implementation in strengthening community-based da’wah in the modern era, as well as to identify the structural, cultural, and ideological problems affecting the movement’s effectiveness. The research employs a qualitative approach using a critical case study design through participatory observation, in-depth interviews, organizational documentation, and discourse analysis of Muhammadiyah policies related to GJDJ. The findings reveal that the implementation of GJDJ experiences fragmentation between ideological ideals and institutional praxis due to the dominance of institutional-oriented charitable enterprises (amal usaha), weak cadre regeneration of community mentors, and the lack of integration of community-based digital da’wah strategies. The study also finds that revitalizing GJDJ requires reconstructing a more adaptive, collaborative, and socio-participatory model of da’wah in order to remain relevant within modern society. The novelty of this research lies in the development of an integrative model combining community da’wah, social empowerment, and digital transformation within the framework of Muhammadiyah’s modernist Islamic movement